Experience of application of modern laxatives at treatment of functional constipation at adults - Ye. K. Baranskaya (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To estimate efficacy and tolerability of Forlax® in non-interventional observation study as laxative agent at short-term constipation for achievement of one-time laxative effect and at long course treatment of functional chronic constipation at adults in out-patients and hospitalized patients.Material and methods. A short-term constipation, i.e. state functional constipation was diagnosed in 9 patients (constipation caused by compelled bed rest, – in 4 patients, in the first days after admission to hospital – in 5). Duration did not exceed 3–5 days in this subgroup. Chronic functional constipation was diagnosed at 31 patients. The number of defecations per day did not exceed of 2–3 times per week at all patients. Patients received 20 g of macrogoal per day. Time span in hours from the moment of the first dose of forlax intake to the first defecation time was determined individually for each patient (Δt), on the average for the whole group, the optimal dose of drug necessary for the first purging effect was calculated. Duration of the subsequent treatment in the group of constipated patients did not exceed 5–10 days. Patients with chronic constipation received forlax for a month more (30±9 days) on average.Results. The first laxative effect at the majority of patients developed on the second day of treatment. Weighted mean time of purging effect onset was 26 h 40 min (total of Δt for each patient by the moment of first defecation, divided by 40). The average weighted dose of forlax necessary for of the first bowel movement – 30 g of macrogoal. The average frequency of stool on a background of long treatment at patients was 4–6 times per week.Conclusions. Observation demonstrated high clinical efficacy of laxative effect of macrogoal: 38 patents rates the drug as «perfect» and «good» vs 2 as «satisfactory».